2021
DOI: 10.3897/bdj.9.e61349
|View full text |Cite
|
Sign up to set email alerts
|

First records of the pest leaf beetle Chrysolina (Chrysolinopsis) americana (Linnaeus, 1758) (Coleoptera, Chrysomelidae) in Cyprus - a study initiated from social media

Abstract: The leaf beetle Chrysolina (Chrysolinopsis) americana (Linnaeus, 1758), commonly known as the Rosemary beetle, is native to some parts of the Mediterranean region. In the last few decades, it has expanded its distribution to new regions in the North and Eastern Mediterranean basin. Chrysolina americana feeds on plants of the Lamiaceae family, such as Rosmarinus officinalis, Lavandula spp., Salvia spp., Thymus spp. and others. Chrysolina americana is considered a pest, as many of its host plants are of commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…For example, Chrysolina (Chrysolinopsis) americana (Linnaeus, 1758), a pest of Lamiaceae with economic importance, such as Lavandula spp., Salvia rosmarinus and Thymus spp., is native to the Mediterranean region, and has experienced an expansion of its distribution in the last few decades, especially to new regions in the north and eastern Mediterranean basin. 72 Additionally, such a possible shift or even widening in the distribution of L. lusitanica may be accompanied in the future by the arrival of alien leaf beetle species from outside the Iberian Peninsula, favoured by climate change and globalization of trade. Indeed, some of the leaf beetles known to be injurious pests of crops and ornamental plants have already established in Europe in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chrysolina (Chrysolinopsis) americana (Linnaeus, 1758), a pest of Lamiaceae with economic importance, such as Lavandula spp., Salvia rosmarinus and Thymus spp., is native to the Mediterranean region, and has experienced an expansion of its distribution in the last few decades, especially to new regions in the north and eastern Mediterranean basin. 72 Additionally, such a possible shift or even widening in the distribution of L. lusitanica may be accompanied in the future by the arrival of alien leaf beetle species from outside the Iberian Peninsula, favoured by climate change and globalization of trade. Indeed, some of the leaf beetles known to be injurious pests of crops and ornamental plants have already established in Europe in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Nitidulids have been identified both as herbivores and detritivores feeding on ripe and rotten fruit (Georghiou 1977;Jelínek et al 2016). In addition, these families include some easily detectable major pests of ornamental plants, such as the destructive red palm weevil Rhynchophorus ferrugineus (Olivier, 1790) (Kontodimas et al 2006), but also the leaf beetle Chrysolina americana (Linnaeus, 1758), found damaging five aromatic Lamiaceae, including three species native to the island (Hadjiconstantis and Zoumides 2021). Despite the small body size of most species in the aforementioned families, their predominance in the list of alien Coleoptera may well be attributed to their peridomestic lifestyle and negative economic impacts on stored products, crops and ornamentals which reinforce the need for studies addressing their identification and approaches for mitigation of their negative impacts.…”
Section: Biodiversity and Species Richnessmentioning
confidence: 99%
“…Studies addressing the adverse impacts of alien insects in Cyprus mostly focus on insects of agricultural or horticultural significance (Morris 1937;Georghiou 1977;Kontodimas et al 2006;Şişman and Ülgentürk 2010;Ülgentürk et al 2015;Compton et al 2020b;Hadjiconstantis and Zoumides 2021). The impacts of alien insects on the biodiversity of Cyprus has received minimal attention, evidenced by the small number of alien insects (19 species) classified as invasive (Fig.…”
Section: Impactsmentioning
confidence: 99%
“…The phenomenon of social media and nature enthusiasts' apps has prompted the description of new species of spiders, flies, millepedes, grasshoppers and plants (Edwards, 2020;Gonella et al, 2015;Santamaria et al, 2020;Skejo & Caballero, 2016;Winterton, 2020), new locality records (Álvarez-Fidalgo et al, 2018;Mengual & de Soto Molinari, 2020), and new observations of species not recorded for decades (Wilson et al, 2020). Moreover, these platforms can also be very helpful in adding in natura information for museum specimens (Heberling & Isaac, 2018) and in monitoring pest species (Hadjiconstantis & Zoumides, 2021) or exotic species (Kaldari, 2019) distribution over time, which make them of particular interest for ecologists and conservation biologists.…”
Section: Introductionmentioning
confidence: 99%